Retrospective evaluation of 155 adult equids and 21 foals with tetanus from Western, Northern, and Central Europe (2000–2014). Part 2: Prognostic assessment. Issue 6 (28th September 2017) - van Galen, Gaby; Rijckaert, Joke; Mair, Tim; Amory, Helene; Armengou, Lara; Bezdekova, Barbora; Durie, Inge; Findshøj Delany, Rikke; Fouché, Nathalie; Haley, Laura; Hewetson, Michael; van den Hoven, Rene; et al.
Abstract: Objective: To identify prognostic variables for adult equids and foals with tetanus. Design: Multicenter retrospective study (2000–2014). Setting: Twenty Western, Northern, and Central European university teaching hospitals and private referral centers. Animals: One hundred fifty‐five adult equids and 21 foals with tetanus. Interventions: None. Measurements and Main Results: Variables from history and clinical examination were statistically compared between survivors and nonsurvivors (adults: 49 survivors, 85 nonsurvivors; foals: 7 survivors, 10 nonsurvivors). Cases euthanized for financial reasons were excluded. Mortality rates in adults and foals were 68.4% and 66.7%, respectively. Variables associated with survival in adults included: standing, normal intestinal sounds and defecation, voluntarily drinking, eating soft or normal food, lower heart and respiratory rates, high base excess on admission, longer diagnosis time, treatment and hospitalization delay, and mild severity grade. Variables associated with death included: anorexia, dysphagia, dyspnea, low blood potassium concentration on admission, moderate and severe disease grading, development of dysphagia, dyspnea, recumbency and seizures during hospitalization, treatment with glycerol guaiacolate, intravenous fluids, and intravenous glucose solutions. Variables associated with survival in foals included standing on admission, voluntarily eating soft food and drinking, older age, and longer hospitalization delay. Outcome was not different between different tetanus antitoxin (TAT) dosages, although there was a trend of increasing survival rate with increasing TAT dosages. Cases with appropriate vaccination prior to development of tetanus were rare, but had improved outcome and shorter hospitalization. Conclusions: Prognosis for equine tetanus is poor with similar outcome and prognostic factors in foals and adults. The prognostic assessment of cases with tetanus provides clinicians with new evidence‐based information related to patient management. Several prognostic indicators relate to the ability to eat or drink, and more severe clinical signs relate to poor outcome. Increasing intravenous dosages of TAT has no significant effect on outcome, but the positive trend identified may support a recommendation for high intravenous TAT dosages. Further evaluation is warranted.